2020
DOI: 10.24123/jmb.v19i2.435
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Tourists' Motivations on Cognitive, Affective, and Unique Image of Bali

Abstract: This research examines the effect of tourists’ motivations on cognitive, affective and unique image of Bali. The model used for this study adopted from Llodra-Riere, et al. (2015).  The variable of the study consists of information source, motivation, cognitive image, affective image and unique image. The model in this study used six hypotheses. This research is quantitative and causal type research. This study used non-probability and purposive sampling approach, sample characteristics are the Surabaya touris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Tian, 2019;Wang et al, 2016), and (Gartner, 1994) emphasized the importance of the image people associate with destinations based on TIM. On the other hand, Rahardja and Anandya (2020) showed that TIM directly impacts the cognitive image. Likewise, Beerli-Palacio and Mart ın-Santana (2017) showed that affirming escape and intellectual motives immediately and positively affect the cognitive image before and after a visit.…”
Section: Literature Review and Developing Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Tian, 2019;Wang et al, 2016), and (Gartner, 1994) emphasized the importance of the image people associate with destinations based on TIM. On the other hand, Rahardja and Anandya (2020) showed that TIM directly impacts the cognitive image. Likewise, Beerli-Palacio and Mart ın-Santana (2017) showed that affirming escape and intellectual motives immediately and positively affect the cognitive image before and after a visit.…”
Section: Literature Review and Developing Hypothesesmentioning
confidence: 99%
“…And they proposed that this theory incorporates the effects of social media as an information source and perceived security and safety in the construction of PDI. Recently, social media platforms have developed as the most recent communication medium in the tourist industry, considerably influencing people's lives (Lin et al ., 2021; Nazir et al ., 2021; Rahardja and Anandya, 2020). Moreover, tourist-generated content based on social media has played an essential role in tourism (Kislali et al ., 2016; Park and Lee, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies [34] corroborated that the value of the image people associate with destinations is based on TIM. In contrast, Prameswari [8] showed that TIM directly impacts the cognitive image. Beerli [5] showed that escape and intellectual motives positively affects the DI.…”
Section: Literature Review and Developing Hypothesesmentioning
confidence: 91%
“…And they proposed that this theory must incorporate the effects of social media and perceived security and safety (PSAS) in the construction of DI. Recently, social media has become the tourism industry's most popular communication medium, significantly impacting people's lives [8]; tourist-generated content based on social media has also been crucial to tourism [9]. Travelers can post photos, videos, and interactive trip content on social media [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation